Development of Learning Media Flipbook Digital Comic Based on Local Wisdom to Increase Learning Interest - Diana Kusumaningrum; Aisyatul Masruro (EduLine: Journal of Education and Learning Innovation, 2022)
This study aims to determine: (1) the feasibility of digital comic flipbook learning media and (2) increase students' interest in learning using digital flipbook comics based on local wisdom. This research uses RnD (Research and Development) research with ADDIE model consisting of: analysis, design, development, implementation, and evaluation. The subjects of this study were fourth grade students of SDN 01 Tirtomoyo Malang with a total of 29 students. Data collection techniques used are interviews, observations, questionnaires, and documentation. The results showed that, (1) digital flipbook comic media based on local wisdom proved to have a feasibility level based on a validation questionnaire, response questionnaire, and readability questionnaire, (2) the percentage increase in student interest in learning in small groups was 44.5%, and the results the percentage increase in student interest in learning is 44.46%. Based on the results of this study, it can be concluded that the learning media of digital flipbook comics based on local wisdom can increase the learning interest of fourth grade elementary school students.